2016
DOI: 10.1371/journal.pgen.1005954
|View full text |Cite|
|
Sign up to set email alerts
|

Chromosomal-Level Assembly of the Asian Seabass Genome Using Long Sequence Reads and Multi-layered Scaffolding

Abstract: We report here the ~670 Mb genome assembly of the Asian seabass (Lates calcarifer), a tropical marine teleost. We used long-read sequencing augmented by transcriptomics, optical and genetic mapping along with shared synteny from closely related fish species to derive a chromosome-level assembly with a contig N50 size over 1 Mb and scaffold N50 size over 25 Mb that span ~90% of the genome. The population structure of L. calcarifer species complex was analyzed by re-sequencing 61 individuals representing various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
156
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(159 citation statements)
references
References 141 publications
(187 reference statements)
2
156
0
1
Order By: Relevance
“…With the exception of the fragments that had no segregated markers for alignment between LGs and chromosomes, the mismatches were verified consistently by all three family-specific genetic maps, and distributed across five chromosomes of Asian seabass [33]: Chr2, Chr8, Chr9, Chr15 and Chr20 (Fig. 3).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…With the exception of the fragments that had no segregated markers for alignment between LGs and chromosomes, the mismatches were verified consistently by all three family-specific genetic maps, and distributed across five chromosomes of Asian seabass [33]: Chr2, Chr8, Chr9, Chr15 and Chr20 (Fig. 3).…”
Section: Resultsmentioning
confidence: 84%
“…Integration of the integrated consensus genetic map with the contigs assembly (genome assembly version 2) and scaffold assembly (genome assembly version 3) [33], revealed that 814 out of 3807 (21.4%) contigs and 259 out of 2964 (8.7%) scaffolds and/or contigs were anchored onto the map, accounting for 560.9 Mb (88.0% of 637.5 Mb, version 2) and 579.6 Mb (90.5% of 640.2 Mb, version 3) of the total length of reference genome, respectively. Integration of genetic map with genome assembly anchored additional 275 contigs with a total length of 19.9 Mb onto all 24 LGs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a better resolution of such repeats was obtained in Oropetium thomaeum 21 genome assembly, possibly owing to the 15-kb lower end insert size selection, explaining the importance of longer read lengths in obtaining near-perfect assemblies. The potential of PacBio sequence data in long, eukaryotic genomes has been further showcased in the draft genomes of Gorilla gorilla 45 (scaffold N50 of 23.1 Mb), V. angularis 20 (scaffold N50 of 3.0 Mb), O. thomaeum 21 (contig N50 of 2.4 Mb) and Lates calcarifer 46 (scaffold N50 of 1.19 Mb). A rapid increase in PacBio sequencing for similar large-scale assemblies can be expected in the near future.…”
Section: Discussionmentioning
confidence: 99%